A Critical Appraisal of the Legal and Policy Framework for Sustainable Mining in Ethiopia - Hailemariam, Yared (Journal of Sustainable Development Law and Policy, 2025)
The integration of the concept of sustainable mining into major legal frameworks presents a complex challenge of balancing short-term economic gains with the long-term objectives of economic and social development as well as environmental well-being. This article provides a comprehensive analysis of how the Ethiopian legal framework incorporates the principles of sustainable mining. Employing a qualitative research methodology, this study examines the adequacy of the legal framework in addressing sustainability issues arising from mineral resource extraction. Through document analysis, the article investigates the legal challenges associated with achieving sustainable mining practices. It scrutinizes constitutional provisions, mining laws, and policies governing mineral resources in Ethiopia. The findings indicate that the Ethiopian government has made notable efforts to develop a competitive legal framework that ensures that mining activities are conducted in an economically efficient, environmentally conscious, and socially responsible manner. However, this research uncovers significant gaps and inconsistencies within the existing legal framework, which results in uncertainty and confusion among various stakeholders. These problems impede the effective and sustainable management of mineral resources and ultimately undermine their potential contribution to Ethiopia’s economic growth and social development. Considering these findings, this article proposes several recommendations to address the identified legal and practical challenges associated with regulating mineral resources.